Estudo de fases cristalinas com composições Tb2TeO6, Bi6Te2O13+ δ (δ = 0 ou 2), Bi6-xTbxTe2O13+ δ e Bi6Te2-yRyO13+ δ (R= Ti+4, Ce+4 e Si+4) - Ferreira, Katiúscia Daiane (2020)
Bismuth oxide (Bi2O3), tellurium oxide (TeO2) and terbium oxide (Tb4O7) present important thermal, electrical and optical properties, which provide them functionality and applications, besides can generate binary oxides of relevant scientific interest and technological potential. The present work was dedicated to study of the synthesis conditions and physical and chemical properties of the crystalline phases with compositions Tb2TeO6 and Bi6Te2O13+(= 0; 2). Results for the insertion of Tb, Ti, Si and Ce ions in the Bi6-xTbxTe2O13+, Bi6Te2-yTiyO13+, Bi6Te2-ySiyO13+ e Bi6Te2-yCeyO13+ compositions will also be showed in order to investigate the influence on dynamics of obtaining phases. The Tb2TeO6 has an orthorhombic phase stable at room temperature with parameters a = 5.290Å; b = 9.108Å and c = 10.009Å. The thermal analysis of this composition presented a thermal event at 1230 °C, associated to the decomposition of the material and a more complex one between 300 °C and 1100 °C, possibly related to an oxidation reaction of Tb+32Te+6O6 to Tb+42Te+4O6 at high temperatures. The Tb2TeO6 has an optical band gap of 4.36 eV with high reflectance, above 70%, in the near infrared / visible region and good absorption in the ultraviolet. It is a material that has a promising photoluminescence in the green region (λ = 548nm) with two lifetimes for this emission, estimated at values of 32.0 ± 0.6 ns and 27.3 ± 0.2 μs. The internal quantum yield was 0.34%, a low value probably due to the presence of Tb4+ ions kept in the structure after cooling that can quench emission photoluminescence. The Bi6Te2O13+ (=0 or 2) composition has two distinct phases: orthorhombic ( = 2) and cubic ( = 0). The orthorhombic phase (Bi6Te2O15) with parameters a = 22.741Å; b = 10,794 Å; c = 5.306Å is the stable phase at room temperature. The high temperature cubic phase (Bi6Te2O13), with a = 5.589Å, can be maintained in a metastable condition at room temperature for a long period. The kinetic mechanisms have a dominant influence on obtaining of these phases. The orthorhombic Bi6Te2O15 phase has a very high reflectance, above 80% and an optical band gap of 3.28eV. The photoluminescence presented is characteristic of the Bi+3 ions and the transitions of shallow defect levels. Its electrical conductivity is a thermally activated process described by an Arrhenius relation and maybe due to motion of oxygen vacancies across the grain-boundary. Relative permittivity (Ԑr) was 32.9. The synthesis of the samples in the Bi(6-x)TbxTe2O13+ e Bi6Te(2-y)RyO13+, com R= Ti+4, Ce+4 e Si+4 resulted in the formation of multiphase systems for whatever composition or heat treatment applied.